ANALYSIS OF SHALLOW SUBSURFACE AT HYDROCARBON POTENTIAL AREAS IN NORTH ACEH BASED ON ELECTRICAL RESISTIVITY MODEL - Nurul Aflah; Muchlis Muchlis; Syafrizal Idris; Witan O Ardjakusumah (Universitas Syiah Kuala, 2018)
Hydrocarbon prospect area research has been done in North Aceh at two locations. The research aims to analyze subsurface litology using resistivity method. Data acquisition of each location was presented by 330 m line survey. The acquisition process was generated by Super Sting R8/IP and modelled by EarthImager 2D. Oil and gas (NA1) resistivity section showed anomaly at 170 m (x) and 17 m (z) that was identified as minor fault. However, oil seepage was not founded on the location. Fossil locality (NA2) section showed a contrast vertical anomaly (16-90 Ωm) around 90 – 120 m that was identified as a way for the seepage.